METHODOLOGICAL CONCEPT OF DEVELOPMENT OF PROJECT CULTURE OF VOCATIONAL EDUCATION TEACHERS (Innovative professional education, 2023)
The project culture of vocational teachers is characterized by ambiguity and manifests itself in different contexts. Its development is based on the use of a set of provisions and principles of the following methodological approaches: systemic, synergistic, integrative, competence-based, activity-based, subject-subject, acmeological, cultural, andragogical, professionalographic, technological. The significance and feasibility of methodological approaches in solving problems of developing the project culture of vocational teachers are specified.
Keywords: methodological approaches, principles and provisions, project culture, vocational teacher